2012
DOI: 10.1016/j.ijmachtools.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of grinding temperatures using a foil/workpiece thermocouple

Abstract: The high temperature generated in abrasive processes is the main factor responsible for thermal damage to a ground surface. It can be predicted through the thermal balance of the heat fluxes in the process. Such predictions can be experimentally verified using a foil/workpiece thermocouple. To estimate the thermal behaviour of such a sensor, it was dynamically calibrated with a laser beam to measure its frequency response. It was found that the response of the sensor has a time constant dependant on the therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The experimental background temperature was determined by the lower envelope (see Fig. 8) of the signal delivered by the thermocouple [13]. The signals are shown in Fig.…”
Section: Temperature Measurement and Microstructural Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental background temperature was determined by the lower envelope (see Fig. 8) of the signal delivered by the thermocouple [13]. The signals are shown in Fig.…”
Section: Temperature Measurement and Microstructural Characterizationmentioning
confidence: 99%
“…For the modelling under dry grinding condition (sample Td), the thermal load is a triangular heat distribution with a length l e = 4 mm moving at the 2 m·min − 1 workpiece velocity. The mean heat flux q w,m = 29 W·mm −2 was obtained by fitting the FE temperature rise on the experimental temperature curve in the cooling zone behind the arc of contact [13]. Under wet grinding conditions (sample Tw), the fluid cooling is taken into account by using a heat transfer coefficient h. During the wet grinding test (sample Tw), the background temperature largely exceeds the boiling temperature of the cooling fluid (about 100-150°C for water based emulsion), so that burnout occurs and convection in the fluid is greatly reduced.…”
Section: Finite Element Simulation To Determine the Heat Flux Conductmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second method, the junction consists of numerous microcontacts, which are formed directly at the surface by the plastic deformation induced by the grinding grits. Earlier work on the single pole grindable thermocouple (Lefebvre et al, 2006(Lefebvre et al, , 2012 has identified the sources of uncertainty in the temperature measured at the interface: • The thermal inertia: as the response time of the thermocouple (between a few microseconds and a few milliseconds) is considerably less than the contact time of the wheel with the junction (several tens of milliseconds), this error can be ignored for surface grinding. • The intrusive effect of the thermocouple itself: the maximum temperature measured and the absorbed flux depend on the thermophysical properties of the materials used in the thermocouple assembly, the thickness of the junction and the grinding conditions.…”
Section: Measurement Of the Temperature Of The Wheel-coating Interfacementioning
confidence: 99%
“…Besides, thin film thermocouples or foil thermocouples were also utilised in Refs. [2,[37][38][39][40][41], which have the advantages including the extremely small size of the measure junction to capture temperature signals within a very small area [42].…”
Section: Introductionmentioning
confidence: 99%